Association of FV G1691A Polymorphism but not A4070G With Coronary Artery Disease. (March 2018) - Amara, Ahmed; Mrad, Meriem; Sayeh, Aicha; Haggui, Abdeddayem; Lahideb, Dhaker; Fekih-Mrissa, Najiba; Haouala, Habib; Nsiri, Brahim
Coronary artery disease (CAD) is one of the chief causes of death in the world. Several hypotheses have been promoted as for the origin of the disease, among which are genetic predispositions and/or environmental factors. The aim of this study was to determine the effect of factor V (FV) gene polymorphisms (Leiden, G1691A [FVL] and HR2 A4070G) and to analyze their association with traditional risk factors in assessing the risk of CAD. Our study population included 200 Tunisian patients with symptomatic CAD and a control group of 300 participants matched for age and sex. All participants were genotyped for the FVL and HR2 polymorphisms. Multivariate logistic regression was applied to analyze independent factors associated with the risk of CAD. Our analysis showed that the FVL A allele frequency ( P < 10 –3, odds ratio [OR] = 2.81, 95% confidence interval [CI] = 1.6-4.9) and GA genotype ( P < 10 –3, OR = 4.03, 95% CI = 2.1-7.6) are significantly more prevalent among patients with CAD compared to those controls and may be predisposing to CAD. We further found that the FVL mutation is an independent risk factor whose effect is not modified by other factors (smoking, diabetes, hypertension, dyslipidemia, and a family history of CAD) in increasing the risk of the disease. However, analysis of FV HR2 variation does not show any statistically significant association with CAD. The FVL polymorphism may be an independent risk factor for CAD. However, further investigations on these polymorphisms and their possible synergisms with traditional risk factors for CAD could help to ascertain better predictability for CAD susceptibility.